ECO-ECONOMIC INDUSTRIAL SPHERE REGULATION IN THE CONTEXT OF REGIONAL ECONOMY SUSTAINABLE DEVELOPMENT - Andrey E. Safronov (Advanced Engineering Research)
Actual problems of the eco-economic regulation system of economic agents' activity under the conditions of the sustainable development of the region are considered. Promising approaches to the efficient use of the natural-resources potential of the industrial sphere based on the creating motivational mechanism for co-ordinating economic and ecological interests in reaching managerial decisions are offered.